Polemical Exegesis and Hermeneutical Analysis in Misbah Mustofa’s Tafsir Al-Iklīl - Pratama, Aunillah Reza; Baidowi, Ahmad; Isnaini, Subi Nur; Sayhbana, Moch Nur Syahruz (Analisa: Journal of Social Science and Religion, 2025)
This article analyzes the polemical character of KH. Misbah Mustofa’s Qur’anic interpretation in Tafsir Al-Iklīl, emphasizing his critique of socio-religious authority. The study investigates how a pesantren-based scholar could produce confrontational interpretations and how this attitude is shaped by his pre-understanding of taqlid. Employing a qualitative textual analysis informed by Hans-Georg Gadamer’s philosophical hermeneutics, this research demonstrates that Misbah conceptualizes taqlid not as blind imitation but as adherence to established opinions of qualified mujtahid imams. This pre-understanding becomes a hermeneutical horizon that leads him to reject non-mujtahid authorities whose fatwas dominate public practice. As a result, his tafsir articulates polemical critiques toward religious leaders, institutions, and popular practices, including the ritual use of loudspeakers, exaggerated veneration of scholars, and the Musabaqah Tilawatil Qur’an (MTQ). Misbah’s interpretation thus reflects a fusion of horizons between the Qur’anic text and the dynamics of Javanese Islamic society, producing a critique rooted in the legitimacy of madhhab authority. Theoretically, this research offers a Gadamerian perspective on taqlid as a productive pre-understanding in Nusantara tafsir studies. Practically, it highlights the role of Qur’anic exegesis as an instrument of socio-religious critique and reform.